Unplanned vs. planned peritoneal dialysis as initial therapy for dialysis patients in chronic kidney replacement therapy - Mendes, Marcela Lara; Alves, Camila Albuquerque; Marinho, Laudilene Cristina Rebello; Dias, Dayana Bitencourt; Ponce, Daniela (Springer Nature, 2021)
Aim: To compare infectious and mechanical complications, technique failure and mortality of a planned PD vs. an unplanned PD program. Design: It was a prospective observational study that included chronic kidney disease (CKD) patients who started PD according to medical recommendation: group1—planned and group 2—unplanned PD. Methods: This study evaluated patients who started planned and unplanned PD programs in a teaching hospital from July 2014 to December 2017. Results: A total of 58 patients were included in the planned PD group and 113 in the unplanned PD group. There was difference between the two groups in leak and hospital admissions, that were more frequent in the unplanned PD group. Periods free from exite site infection, peritonitis and mechanical complications were longer in the planned group. Cox regression analysis identified age and the lowest albumin value as factors associated with mechanical complications; peritonitis indicated the presence of ESI and mechanical complications; the change to HD was associated with a younger age, mechanical complications, diabetes mellitus (DM) and peritonitis. The factors associated with death were age and lower values of albumin. After 48 months, the growth of the PD program was 252%. Conclusion: The technique survival and patient mortality in unplanned PD was similar to planned PD, while the period marked by the absence of complications related to PD was longer in the planned PD group. In the Cox regression, unplanned PD was not identified as risk factor for death, transition to HD or complications related to therapy, while age and lower albumin values were predictors of negative outcomes. Impact: Unplanned PD is not risk factor for death and complications related to PD and can be an option to unplanned HD.
Keywords: Dialysis; Nursing home care; Peritoneal dialysis